2018
DOI: 10.18203/2394-6040.ijcmph20184814
|View full text |Cite
|
Sign up to set email alerts
|

A study on animal bites and envenomings in rural Varanasi: a community based cross-sectional study

Abstract: Background: Animal bites are major public health issues in children and adults worldwide. The most important bites are by dogs, cats and monkeys that may cause rabies. Globally, approximately 60,000 annual deaths occur from rabies. Another important bite is by snakes. In India, approximately 94,000–1,25,000 deaths occur by snake bites annually. Therefore, we undertook this study to estimate the incidence of animal bites and to determine the treatment seeking behaviour of victims of animal bites.Methods: It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Our study found that the demand for the unmet need for spacing and limiting was the highest among women aged 15-19 and 20-24. Several previous studies have documented the contrary to this finding showing evidence between age at marriage and current age with the unmet need for family planning [25][26][27][28][29] . They revealed that the odds of a total unmet need for family planning were higher among women aged 40-49 (AOR = 1.33*) than those aged 15-29.…”
Section: Discussionmentioning
confidence: 80%
“…Our study found that the demand for the unmet need for spacing and limiting was the highest among women aged 15-19 and 20-24. Several previous studies have documented the contrary to this finding showing evidence between age at marriage and current age with the unmet need for family planning [25][26][27][28][29] . They revealed that the odds of a total unmet need for family planning were higher among women aged 40-49 (AOR = 1.33*) than those aged 15-29.…”
Section: Discussionmentioning
confidence: 80%
“…Male individuals, particularly adults in the age group of 20-39, were the most vulnerable to animal bites. 1 Children aged 5-12 were more exposed to animal bites compared to teenagers (13)(14)(15)(16)(17)(18)(19)) and (10)(11). Most victims belonged to the Above Poverty Line (APL) socioeconomic category, followed by Below Poverty Line (BPL) and other categories.…”
Section: Demographics and Socioeconomic Factorsmentioning
confidence: 99%